Corrosion behaviour characterisation of 316L stainless steel and Inconel 625 in supercritical water containing hydrochloric acid and high oxygen. (3rd October 2022) - Zhou, Hongyi; Tian, Zhao; Liao, Chuanhua
ABSTRACT: Corrosion was currently the most crucial factor hindering the commercial development of supercritical water oxidation (SCWO) technology. Stainless steel represented by 316L and Ni-based alloy represented by Inconel 625 were performed and compared with corrosion resistance in supercritical environment with high concentrations of oxygen and chlorides. The results shown that the duplex layer was formed on two samples. The surface of 316L SS was mainly composed of loose magnetite and haematite, resulted in pitting corrosion, microcracks, and the exfoliation of oxide. The inner layer were separately a small amount of Cr2 O3 oxide and FeCr2 O4 spinel, which were caused by the lower content of chromium. Compared with 316L SS, the oxide film structure of Inconel 625 was composed of the outer layer of spinel and the inner layer of Cr-rich oxide. Some nodular oxides were formed, and it can be explained by the volatilisation process of chromium.